Towards the development of potent therapy against the hepatitis C virus - Neyts, Johan (Henry Stewart Talks, 2011)
The HCV genome and replication cycle, Interferon development, Ribavirin, Antiviral and GTP depletion correlation, Selective inhibitors of HCV replication, The NS2 cysteine and the NS3 serine proteases, Protease inhibitors, The NS3 helicase as an antiviral target, NS4A/NS3, NS4B and NS5A as antiviral targets, The NS5B RNA dependent RNA polymerase, Nucleoside and non-nucleoside HCV inhibitors, Double and triple combination therapies, Debio-025, Resistance to HCV inhibitors, D320E peptide mutation effect, Role of NS5A or NS5B in resistance, Wild type and CypA knock down studies, Cis-trans isomerase activity of cyclophilins
Archived at 2021/02/25